Suppression of NLR-mediated plant immune detection by bacterial pathogens. - Rufián Plaza, José Sebastián; Rueda-Blanco, Javier; Beuzón-López, Carmen del Rosario; Ruiz-Albert, Francisco Javier (Oxford University Press, 2023)
The plant immune system is constituted of two functionally interdependent branches that provide the plant with an effective defense against microbial pathogens. They can be considered separate since one detects extracellular pathogen-associated molecular patterns by means of receptors on the plant surface, while the other detects pathogen- secreted virulence effectors via intracellular receptors. Plant defense depending on both branches can be effectively suppressed by host-adapted microbial pathogens. In this review we focus on bacterially driven suppression of the latter, known as effector-triggered immunity (ETI) and dependent on diverse NOD-like receptors (NLRs). We examine how some effectors secreted by pathogenic bacteria carrying type III secretion systems can be subject to specific NLR-mediated detection, which can be evaded by the action of additional co-secreted effectors (suppressors), implying that virulence depends on the coordinated action of the whole repertoire of effectors of any given bacterium and their complex epistatic interactions within the plant. We consider how ETI activation can be avoided by using suppressors to directly alter compromised co-secreted effectors, modify plant defense-associated proteins, or occasionally both. We also comment on the potential assembly within the plant cell of multi-protein complexes comprising both bacterial effectors and defense protein targets.
Keywords: Bacterias fitopatógenas; Plantas - Metabolismo; Bacterial effectors; Defense evasion; Defense suppression; Effector-triggered immunity; NLR proteins; PAMP-triggered immunity; Plant immunity; Type III secretion system